“Old Lecher, it’s Time for You to the Grave…” – Late Elegies (?) by Czesław Miłosz - Olejniczak , Józef (Archiwum Emigracji. Studia – Szkice – Dokumenty, 2024)
English version. Original issue: “Archiwum Emigracji” 2007, no. 1 (9) https://www.bu.umk.pl/Archiwum_Emigracji/gazeta/ae_9.pdf